Induced effect of zinc oxide nanoparticles on human acute myeloid leukemia cell apoptosis by regulating mitochondrial division. Issue 6 (23rd April 2022) - Yin, Xuewei; Li, Zonghong; Lyu, Chunyi; Wang, Yan; Ding, Shumin; Ma, Chenchen; Wang, Jingyi; Cui, Siyuan; Wang, Jinxin; Guo, Dadong; Xu, Ruirong
Abstract: Zinc oxide nanoparticles (ZnO NPs) have exhibited excellent anti‐tumor properties; the present study aimed to elucidate the underlying mechanism of ZnO NPs induced apoptosis in acute myeloid leukemia (AML) cells by regulating mitochondrial division. THP‐1 cells, an AML cell line, were first incubated with different concentrations of ZnO NPs for 24 hr. Next, the expression of Drp‐1, Bcl‐2, Bax mRNA, and protein was detected, and the effects of ZnO NPs on the levels of reactive oxygen species (ROS), mitochondrial membrane potential (Δψm), apoptosis, and ATP generation in THP‐1 cells were measured. Moreover, the effect of Drp‐1 inhibitor Mdivi‐1 and ZnO NPs on THP‐1 cells was also detected. The results showed that the THP‐1 cells survival rate decreased with the increment of ZnO NPs concentration and incubation time in a dose‐ and time‐dependent manner. ZnO NPs can reduce the cell Δψm and ATP levels, induce ROS production, and increase the levels of mitochondrial division and apoptosis. In contrast, the apoptotic level was significantly reduced after intervention of Drp‐1 inhibitor, suggesting that ZnO NPs can induce the apoptosis of THP‐1 cells by regulating mitochondrial division. Overall, ZnO NPs may provide a new basis and idea for treating human acute myeloid leukemia in clinical practice.